Direction‐Reversible Accelerated Beam Generation Based on Metasurfaces. Issue 9 (4th August 2022) - Lu, Peiyao; Zhou, Changda; Xu, Jilian; Yue, Zhiyuan; Li, Zhong; Teng, Shuyun
Abstract: Accelerated beams have many applications because of their remarkable ability to propagate along curved trajectories. An accelerated beam with a non‐monotonic trajectory provides more beam deformability and trajectory concealment. This paper proposes direction‐reversible accelerated beam generation on nanometer scale based on metasurfaces. The non‐monotonic trajectory of the beam can be obtained by designing the geometric metasurface, while the curvature of the light trajectory can be adjusted by changing the angles of rectangular nanoholes. A theoretical expression for the modified wavefront of the proposed beam is deduced, and simulation and experiment results confirm the performance of the metasurface for generating a direction‐reversible accelerated beam. Discussions on the self‐healing of the accelerated beam and the influence of incident conditions on the curve trajectory show the trajectory controllability of the accelerated beam during the propagation. This work paves one way for tailoring the accelerated fields with complex trajectories, and it is helpful to expand the applications of accelerated beams. Abstract : This paper provides the analytic expression of the wavefront of a direction‐reversible accelerated beam, which avoids complex integration operations or spatial transformation, and enables the concise design of geometric metasurfaces to generate direction‐reversible accelerated beams.